Implementasi Pendidikan Berkelanjutan melalui Literasi Lingkungan dalam Kurikulum Sekolah Dasar - Sahil Gunawan; Irpan Juanda; Sheyla Amanda (Jurnal Pacu Pendidikan Dasar, 2025)
This study aims to analyze the implementation of environmental literacy through sustainability education in the elementary school curriculum and identify factors influencing its success. The study used a qualitative approach with a descriptive design in an elementary school that has integrated environmental education into learning and school culture. Data were collected through observation, in-depth interviews, and documentation, then analyzed using systematic reduction, presentation, and conclusion-drawing techniques. The results showed that environmental literacy was implemented through cross-disciplinary integration, experiential learning, and strengthening a school culture that supports environmentally friendly behavior. Students experienced improvements in environmental knowledge, attitudes, and skills, although participation remained variable. Supporting factors included teacher competence, school policies, and community involvement, while constraints included limited resources, lack of teacher training, and suboptimal curriculum integration. This study concluded that environmental literacy through sustainability education requires an integrated approach between curriculum, learning, school culture, and community participation to achieve optimal results.